Pediatric Developmental Coordination Disorder Screening and Assessment: Emerging Roles of Technology - Kristen De Melo; Julia De Oliveira; Ewa Niechwiej-Szwedo; Nadja Schott; Lori Ann Vallis (Clinical Pediatrics, 2026)
Throughout childhood, cognitive and motor skill development are tightly linked; thus, early skill assessment is crucial to capture functional delay and/or atypical development. One condition challenging to identify is developmental coordination disorder (DCD). Cognitive and motor function assessments are often performed separately, using different tools and tests, making results less generalizable to real-world, ecological settings that require integrated sensorimotor and cognitive control. Technological advances may facilitate more accurate, precise, and objective skill assessment. The objective of this scoping review was to summarize the frequency and types of technology used in laboratory-based assessments of cognitive and sensorimotor function in children and adolescents diagnosed with DCD. Published studies were reviewed, and assessment tools were categorized by functional purpose while outcome measures were identified. Data synthesis revealed various laboratory-based methods often studied cognitive and motor processes as separate entities. Findings highlight the growing use of technology and the need for more integrated DCD assessment.